Discipleship Based On Logical Teaching From Internal And External To Improve The Spiritual And Social Behaviour Of Pentecostal-Charismatic Congregations - Mardona Bangun; Juwita Barutu; Tiopan Tampubolon (International Journal Labs, 2023)
Discipleship is at the church's heart, the congregation's maturation. Discipleship requires much energy, thought, time, and money, so few like it and can survive. Pentecostal-charismatic discipleship is not severe in teaching because it focuses on the feelings and number of people/churches. The ministers involved are often less qualified in theological education, so the activities carried out in Bible study are more inclined to strengthen the bonds of the congregation through sharing activities and sermons just talking about morals and success in life. Discipleship should focus on who Jesus is, the logician, not on what Jesus did, so it falls to the teaching of the power of words; that is, people can imitate everything Jesus did. This study used a quantitative approach to 258 respondents whose results were that the congregation could not distinguish true and untrue servants of God. False faith in Jesus, like the apostles' faith before Pentecost, is considered the absence of faith. The involvement of pastors and congregations outside Pentecostal-charismatic is urgent to improve the spiritual and social behavior of Pentecostal-charismatic congregations.